Sunday

December 21, 2014

December 21, 2014

Posted by **al** on Thursday, January 13, 2011 at 12:59am.

4x + 3y = 3

7x - 9y = 6

- math -
**Reiny**, Thursday, January 13, 2011 at 8:41amfrom the 1st

3y = 3-4x

or 9y = 9 - 12x

now sub that into the 2nd

7x - (9-12x) = 6

19x = 15

x = 15/19

back into 3y = 3-4x

3y = 3 - 60/19 = -3/19

y = -1/19

**Answer this Question**

**Related Questions**

Calculus 2 - Evalute the integral of x/(x^2+4)dx using u-substitution and then ...

Trigonometric Substitution - Trigonometric Substitution a. Explain why the ...

math - int 1/ (sq rt (4sec^2 x +4)) dx trigonometric substitution expression: sq...

math - solve each system of equations by substitution. y=3x-9 please help ...

Math - 1. Explain the advantages and disadvantages of both the substitution ...

calculus - Integrate x/(x^2 + 4) dx via trig substitution and by u=x^2+4 ...

math/ elimination& substitution - how do i solve this? using elimination or ...

math substitution method - use the substitution method to solve 7x+5y=-26 x=28-...

calculus - We're doing indefinite integrals using the substitution rule right ...

Algebraic Systems - Okay i just wanna know what you think is the easiest between...